Analysis of Delay Factors in the Capital Expenditure Package and Public Facilities Project of Turyapada Tower Technology Park KBS 6.0 Kerthi Bali - Rinto Herdiman Sitorus; Saputra, Rifaldi Adi (Jurnal Ilmiah Teknik, 2025)
Delays in construction projects often impact cost, time, and quality. This study was conducted on the Turyapada Tower Technology Park KBS 6.0 Kerthi Bali project, which experienced delays from its initial schedule. The aim of the research is to identify and analyze the dominant factors contributing to project delays. Using a quantitative method through questionnaires distributed to 50 respondents and data analysis with validity tests, reliability tests, and Pearson correlation in SPSS, the results indicate that environmental and equipment factors are the primary causes of delays, followed by labor, management, execution methods, and materials. The dominant factors show a very strong correlation with project schedule delays. These findings are expected to serve as an evaluation and input to improve timeliness and efficiency in similar projects in the future.